1991
DOI: 10.1029/91jd00993
|View full text |Cite
|
Sign up to set email alerts
|

Ozone budget over the Amazon: Regional effects from biomass‐burning emissions

Abstract: A one‐dimensional, time‐dependent, photochemical model is used in conjunction with data obtained during the dry‐season portion of NASA's Global Tropospheric Experiment and Brazil's Instituto Nacional de Pesquisas Espaciais (INPE) (National Institute for Space Research) Amazon Boundary Layer Experiment (ABLE 2A) to simulate the chemistry of the dry‐season Amazon troposphere. The background atmosphere, unperturbed by the presence of emissions from biomass burning, is simulated with inputs of surface sources and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Our calculation of net column production for the 2-11 km layer in the Case 3 undisturbed conditions is 4.4 x 1011 molec cm-2 s-1. Richardson et al [1991] computed tropospheric column 03 production to be 4.4 x 1011 cm-2s-1 in regions containing polluted layers (up to 1000 km distant from buming activity) in ABLE 2A, which is comparable to the 0-13 km integrated value we have computed for Case 1 undisturbed conditions [Pickering et al, 1991] Ozone production rates (in ppb/day) averaged over the 5-13 km layer are shown in Table 5 for the cloud-processed conditions in the three cases. The ozone loss term, O(1D) + H20, had values ranging from 2.7 to 8.3 times greater than were computed by Crutzen et al [1985] for the drier environment of nonconvective conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Our calculation of net column production for the 2-11 km layer in the Case 3 undisturbed conditions is 4.4 x 1011 molec cm-2 s-1. Richardson et al [1991] computed tropospheric column 03 production to be 4.4 x 1011 cm-2s-1 in regions containing polluted layers (up to 1000 km distant from buming activity) in ABLE 2A, which is comparable to the 0-13 km integrated value we have computed for Case 1 undisturbed conditions [Pickering et al, 1991] Ozone production rates (in ppb/day) averaged over the 5-13 km layer are shown in Table 5 for the cloud-processed conditions in the three cases. The ozone loss term, O(1D) + H20, had values ranging from 2.7 to 8.3 times greater than were computed by Crutzen et al [1985] for the drier environment of nonconvective conditions.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, in this simplified exercise, high initial levels of HCHO significantly reduce the time period during which emissions containing high NOx could be uplifted to the free troposphere. In addition, more 03 is made "early" and is thus subject to cloud scavenging during a deep convection event [Chatfield and Delaney, 1990; Richardson et al, 1991;Lelieveld et al, 1997]. If these turn out to be general effects of oxygenated compounds in real plumes, then the amount of 03 produced could be greatly reduced.…”
Section: Influence Of Oxygenated Organic Compounds On Initial Plume Cmentioning
confidence: 97%
“…Numerous investigations of the atmospheric impact of tropical fires have given clear evidence that elevated levels of ozone over South America and Africa are due to the excessive burning of forests and savannah, the rain forest otherwise acting as an important net sink for ozone (e.g., Delany et al, 1985;Browell et al, 1988;Gregory et al, 1988;Crutzen and Andreae, 1990;Richardson et al, 1991;Kirchhoff and Marinho, 1994;Kirchhoff, 1996;Kirchhoff et al, 1996). A retrieval of satellite measurements has given evidence of substantial ozone export to the tropical oceanic regions (Fishman et al, 1986;Fishman and Larsen, 1987), a strong burden to the otherwise clean troposphere in the Southern Hemisphere during certain periods of the year.…”
Section: Introductionmentioning
confidence: 99%